NAAG Detection in the Human Brain at 7T by TE Optimization and Improved Wiener Filtering - An, Li (2013)
PURPOSE: We report enhanced signal detection for measuring N-acetyl-aspartyl-glutamate (NAAG) in the human brain at 7T by TE-optimized point-resolved spectroscopy (PRESS) and improved Wiener filtering. METHODS: Using a highly efficient in-house developed numerical simulation program, a PRESS sequence with (TE(1), TE(2)) = (26, 72) ms was found to maximize the NAAG signals relative to the overlapping Glu signals. A new Wiener filtering water reference deconvolution method was developed to reduce broadening and distortions of metabolite peaks caused by B(0) inhomogeneity and eddy currents. RESULTS: Monte Carlo simulation results demonstrated that the new Wiener filtering method offered higher spectral resolution, reduced spectral artifacts, and higher accuracy in NAAG quantification compared to the original Wiener filtering method. In vivo spectra and point spread functions of signal distortion confirmed that the new Wiener filtering method lead to improved spectral resolution and reduced spectral artifacts. CONCLUSIONS: TE-optimized PRESS in combination with a new Wiener filtering method made it possible to fully utilize both the NAAG singlet signal at 2.05 ppm and the NAAG multiplet signal at 2.18 ppm in the quantification of NAAG. A more accurate characterization of lineshape distortion for Wiener filtering needs B(0) field maps and segmented anatomical images to exclude contribution from cerebral spinal fluid.